Enhancing Kindergarten Students' Speech Skill Through the Use of Picture Stories - Sri Slamet; Markhamah Markhamah; Salma Zhafirah Yasri; Rumaisha Faradilla Ardyani (Universitas Negeri Semarang, 2024)
Action research was conducted to determine whether speaking ability was improving among Mardisiwi Islamic Students in Surakarta by using picture stories. 15 students participated as the study's subject. This study was conducted over the course of two cycles and four sessions. Planning, action, analysis, and reflection were the four steps that it went through. The information related to picture stories' use in teaching and learning as well as the students' oral communication skills. The research's data were gathered through documentation, observation, and interviews. They were gathered using two cycles, each of which had two meetings. The effectiveness of the students' Mardisiwi Islamic kindergarten speaking is determined by the outcomes of the acts that were done in Cycles I and II. Based on the outcomes of the measures taken in Cycles I and II, the Mardisiwi Islamic Kindergarten children' speaking abilities increased. The data showed that just 40% of students were Developing as Expected (DAE) before the action's implementation, but that number increased to 73.3% and 86.6% in Cycles I and II, respectively. According to the findings of this study, children at Mardisiwi Islamic Kindergarten in Surakarta, Indonesia, were better able to understand language learning due to the usage of picture story media. In addition to documenting the pedagogical benefits of picture story media, this research introduces a novel perspective on enhancing speaking abilities among kindergarten students, offering valuable insights for educators and researchers alike.